Layer-specific high-frequency action potential spiking in the prefrontal cortex of awake rats - Boudewijns, Zimbo S.; Groen, Martine; Lodder, Brendan; McMaster, Minni; Kalogreades, Lawrence; de Haan, Roel; Narayanan, Rajeev; Meredith, Rhiannon; Mansvelder, Huibert; de Kock, Christiaan P. (Frontiers in Cellular Neuroscience, 2013)
Cortical pyramidal neurons show irregular in vivo action potential (AP) spiking with high-frequency bursts occurring on sparse background activity. Somatic APs can backpropagate from soma into basal and apical dendrites and locally generate dendritic calcium spikes. The critical AP frequency for generation of such dendritic calcium spikes can be very different depending on cell type or brain area involved. Previously, it was shown in vitro that calcium electrogenesis can be induced in L(ayer) 5 pyramidal neurons of prefrontal cortex (PFC). It remains an open question whether somatic burst spiking and the resulting dendritic calcium electrogenesis also occur in morphologically more compact L2/3 pyramidal neurons. Furthermore, it is not known whether critical frequencies that trigger dendritic calcium electrogenesis occur in PFC under awake conditions in vivo. Here, we addressed these issues and found that pyramidal neurons in both PFC L2/3 and L5 in awake rats spike APs in short bursts but with different probabilities. The critical frequency (CF) for calcium electrogenesis in vitro was layer-specific and lower in L5 neurons compared to L2/3. Taking the in vitro CF as a predictive measure for dendritic electrogenesis during in vivo spontaneous activity, supracritical bursts in vivo were observed in a larger fraction of L5 neurons compared to L2/3 neurons but with similar incidence within these subpopulations. Together, these results show that in PFC of awake rats, AP spiking occurs at frequencies that are relevant for dendritic calcium electrogenesis and suggest that in awake rat PFC, dendritic calcium electrogenesis may be involved in neuronal computation.